Automated design framework for excavation retaining structures: Extending IFC standards and integrating BIM with geotechnical simulation - Qiwei Wan; Yuyuan Zhu; Haibin Ding; Wentao Hu; Changjie Xu (Underground Space)
Challenges arise in automate design with building information modeling (BIM) in underground space. Industry foundation classes (IFC) standard lacks detailed entity objects for describing excavation retaining structures and geological information, and automated design based on BIM models is not yet for practical application. This study presents a novel automated framework. It integrates the extended IFC standard with mechanical analysis and BIM modeling, significantly advancing structural optimization and rebar detailing. Direct 3D model generation streamlines complex excavation projects, aligning with the trend towards automated, precision-driven design. Key contributions include: (1) the extension of the IFC standard to support excavation retaining structures with objects like IfcBracedPit and IfcPitWall, improving interoperability between geotechnical models and BIM systems; (2) the integration of heuristic algorithms for automated optimization of deformation control parameters, reducing manual intervention; and (3) the promotion of design methodology that bypasses two-dimensional modeling and directly generates three-dimensional models, enhancing efficiency and allowing engineers to focus on high-level decision-making. However, the framework is primarily suited for standard cross-section projects like subway stations and tunnels. Future work will focus on refining the framework for more complex geotechnical projects, addressing software independence and improving design robustness and independence.